Haptics: Perception, Devices, Mobility, and Communication 8th International Conference, EuroHaptics 2012, Tampere, Finland, June 13-15, 2012 Proceedings, Part II - Isokoski, Poika; Springare, Jukka (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
This book and its companion volume, LNCS 7282 and 7283, constitute the refereed proceedings of the 8th International Conference, EuroHaptics 2012, held in Tampere, Finland, in June 2012. The 99 papers (56 full papers, 32 short papers, and 11 demo papers) presented were carefully reviewed and selected from 153 submissions. Part I contains the full papers whereas Part II contains the short papers and the demo papers.